Salvage therapy with an Albuvirtide-based antiretroviral regimen for multi-drug resistant HIV and drug-resistant HBV with renal impairment: a case report - Yaozu He; Baolin Liao; Yuantao Liu; Yang Cao; Linghua Li; Weiping Cai (Virology Journal)
Abstract Background The clinical management of HIV, particularly in the context of multi-drug resistance (MDR) and co-infections such as hepatitis B virus (HBV), is notably complex. Here we present a case study of a patient with multi-drug resistant HIV who was co-infected with drug-resistant HBV and suffered from renal insufficiency. We employed an optimized regimen based on the fusion inhibitor Albuvirtide (ABT), combined with highly effective, low nephrotoxicity antiviral drugs for HBV. This approach ultimately achieved effective suppression of both HIV and HBV. Case presentation A 58-year-old male, diagnosed with HIV in 1997 and co-infected with HBV, experienced renal insufficiency. Due to poor adherence, he developed resistance to nucleoside, non-nucleoside reverse transcriptase inhibitors, and protease inhibitors over nearly two decades, necessitating frequent modifications to his ART regimen. In 2019, HIV RNA rebounded to 1120 copies/mL, prompting resistance testing that revealed high-level resistance to Elvitegravir (EVG), intermediate resistance to Raltegravir (RAL), and potential low-level resistance to Bictegravir (BIC) and dolutegravir (DTG). This led to a strategic overhaul of the ART to ABT + Emtricitabine/Tenofovir Alafenamide (FTC/TAF) + double-dose DTG, resulting in a significant suppression of the HIV. Concurrently, HBV suppression and renal function were well-maintained. Conclusions This case underscores the potential value of individualized treatment strategies for patients with multidrug-resistant HIV and HBV co-infection complicated by renal impairment. The observed virological control following the use of novel agents such as Albuvirtide (ABT), in combination with second-generation integrase strand transfer inhibitors (INSTIs) like DTG, alongside renal-sparing antivirals, highlights the importance of designing optimized regimens based on resistance profiles and renal function. This personalized and adaptive therapeutic approach may offer clinical benefits in similarly complex scenarios.